Access and Utilization of Maternal Health Care Services among Rural Mothers in Sahid Lakhan Rural Municipality, Gorkha, Nepal - Devkota, Bijaya Mani; Acharya, Suresh (Rural Development Journal, 2026)
The use of the maternal health services is a significant national health issue in rural Nepal, which faces a significant number of inadequate infrastructures, and social-economic factors. Despite the improvement of maternal health indicators at the national health level, large disparities continue to remain in the remote districts like Sahid Lakhan Rural Municipality of Gorkha District. This study to evaluate the use of prenatal, birth, and postnatal care services. This study involved 160 households in the Ward No. 4 that analysis descriptive statistics and tests of chi-square were used. The results showed that 86 percent of mothers had four or more visits to the antenatal care, with 89.3 percent as large percentage said that they took iron pills throughout at least 100 days (85.4%), had two doses of tetanus toxoid vaccination (73.6%), and took anti-worming medication (88.2%). Sixty-nine point one percent of the respondents reported institutional delivery, whereas 30.9 percent delivered at home primarily because of distance and cost of transport; skilled attendance at birth had been experienced in 73 percent. The use of post-partum care was low and only 59 percent of had at least one post-partum care visit, although colostrum feeding and vitamin A were highly practiced (94.4% and 83.1 %). The use of maternal health services was also found to be strongly linked with the level of education of women, the number of children, and the distance to health facilities, indicating that the gaps in post-partum and safe delivery care.